Whitefly (Bemisia tabaci) Management Program for Ornamental Plants - Vivek Kumar; Christi Palmer; Cindy L. McKenzie; Lance S. Osborne (EDIS)
Provides management recommendations, strategies for detection and scouting, and advice about control measures for Bemisia tabaci.